2020
DOI: 10.3390/agronomy10071011
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Oxytetracycline and Chlortetracycline on Bacterial Community Growth in Agricultural Soils

Abstract: Toxicity on soil bacterial community growth caused by the antibiotics oxytetracycline (OTC) and chlortetracycline (CTC) was studied in 22 agricultural soils after 1, 8 and 42 incubation days. The leucine incorporation method was used with this aim, estimating the concentration of each antibiotic which caused an inhibition of 50% in bacterial community growth (log IC50). For OTC, the mean log IC50 was 2.70, 2.81, 2.84 for each of the three incubation times, while the values were 2.05, 2.22 and 2.47 for CTC, mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 50 publications
(68 reference statements)
4
15
0
Order By: Relevance
“…However, in soil 2 (Figure 2), the bacterial community growth decreased for the higher SDZ doses, achieving significant reductions in relation to the control for the doses of 500 and 2000 mg•kg −1 . However, the magnitude of decrease for the highest SDZ dose (2000 mg•kg −1 ) was relatively low (32%), if compared with results previously reported for other antibiotics, such as tylosin [33,41], tetracyclines [22,28,29,33], or streptomycin [22]. It is worth noting that, despite the low adsorption previously reported for SDZ onto soils [42], the short-term effect of SDZ on bacterial community growth was relatively low.…”
Section: Data Analysis and Statisticsmentioning
confidence: 47%
See 2 more Smart Citations
“…However, in soil 2 (Figure 2), the bacterial community growth decreased for the higher SDZ doses, achieving significant reductions in relation to the control for the doses of 500 and 2000 mg•kg −1 . However, the magnitude of decrease for the highest SDZ dose (2000 mg•kg −1 ) was relatively low (32%), if compared with results previously reported for other antibiotics, such as tylosin [33,41], tetracyclines [22,28,29,33], or streptomycin [22]. It is worth noting that, despite the low adsorption previously reported for SDZ onto soils [42], the short-term effect of SDZ on bacterial community growth was relatively low.…”
Section: Data Analysis and Statisticsmentioning
confidence: 47%
“…These results can be considered somehow surprising, since organic compounds (including antibiotics) generally decrease their toxicity with time. As examples, decreases in toxicity of organic compounds were previously found for atrazine when examining effects on microbial biomass [46], as well as for fomesafen regarding effects on urease activity [47], or tetracycline regarding its effect on bacterial community tolerance [28,29]. This decrease is reasonable, since the concentrations of these organic compounds were reduced with time due to degradation [48], or suffered immobilization in the soil via ageing processes [49], or microbial communities developed tolerance to the organic compound [50].…”
Section: Data Analysis and Statisticsmentioning
confidence: 86%
See 1 more Smart Citation
“…The final antibiotic concentrations (for CTC, TC, and OTC) in each soil were 0.00, 0.49, 1.95, 7.81, 31.25, 125, 500, and 2000 mg•kg −1 of soil. The concentrations were previously selected [12] in order to obtain almost complete inhibition of soil bacterial growth, thus offering estimates of to-xicity indices in a more reliable way [16]. The antibiotics were added to the soils using inert talc powder as a carrier for equalizing the amount of dry material added to each soil sample, as well as to facilitate mixing of the substances into soil [17].…”
Section: Experiments Designmentioning
confidence: 99%
“…Santás-Miguel et al [11], in a recent laboratory study, added with different concentrations of tetracycline (TC) to 22 soils incubated under controlled conditions of moisture and temperature for 42 days, and they reported that, initially, tetracycline negatively affected bacterial activity measured by means of the cellular incorporation of labeled leucine, whereas this effect was drastically reduced at the end of the incubation time. Subsequently, Santás-Miguel et al [12] studied the toxicity of oxytetracycline (OTC) and chlortetracycline (CTC) toward bacterial communities for 42 days and observed a negative effect of both antibio-tics on the growth of bacterial communities. The effect of CTC decreased with incubation time; however, the effect of OTC on bacterial communities persisted over time.…”
Section: Introductionmentioning
confidence: 99%